Pengalaman Perawat Dalam Pencegahan Ekstravasasi Pada Pasien Kemoterapi Di Murni Teguh Memorial Hospital - Doloksaribu, Sofia Andari; Simatupang, Lenny Lusia (STIKes Murni Teguh, 2025)
Cancer arises from uncontrolled cell growth, and chemotherapy is one of the therapies. This procedure carries the risk of extravasation, which can cause pain, ulcers, necrosis, and even permanent disability. This condition has the potential to trigger trauma and cause patients to discontinue therapy, ultimately hindering treatment success. Safe chemotherapy practices require nurses to be competent in preventing, recognizing, managing, and documenting extravasation incidents. This qualitative study used a phenomenological method at Murni Teguh Memorial Hospital. The sample size was selected using purposive sampling and interviews. This study yielded six themes regarding nurses' experiences in preventing extravasation in chemotherapy patients. It is concluded that this study identified six themes: (1) Dangers of extravasation, (2) Actions to prevent extravasation, (3) Things that can cause extravasation, (4) Ways to overcome extravasation, (5) Barriers to accessing the verifier vein, and (6) Ways to overcome barriers to accessing the verifier vein.